Advancing Healthcare, Petroleum, Chatgpt, Fraud Detection, and Cybersecurity: The Transformative Role of Artificial Intelligence - Ali, Mohammad (CV. Multi Kreasi Media, 2024)
The results found are that AI is quickly changing the industries with increasing prominence in areas such as health, petroleum fraud identification and cybersecurity. In healthcare, AI to lift the accuracy of diagnosis, of treatment plans and of drug development, directly enhancing patients’ quality and outcomes. AI is set to reform the way petroleum’s sector identifies frauds and prevents them by detecting fraud cases, ensuring transparency and integrating with other technologies such as block chain. Likewise, AI is taking a more strategic stance within cybersecurity as threats are detected, analyzed and projected, wherein its use presents organizations with powerful preventative solutions for their data and structures. Nevertheless, with the growing use of AI in these sectors there arises important ethical questions that need to be answered. Such include issues to do with privacy, security of data, fairness of algorithms and the inherent requirement of human supervision. Health care related artificial intelligence systems should respect patient rights to privacy and avoid compromise of such rights as well as ensure that it does not have pre – coded biases affecting operations of vulnerable patients. Surveillance, accountability and transparency themes hence play major roles in analyzing fraud detection in the petroleum sector for a secure fair process. In cybersecurity, there is a problem of proportioning privacy with the accessibility of security; another challenge is controlling adversarial attacks on the AI systems; or maintaining human supervision in the decision-making processes dominated by AI. Chatgpt sophisticated natural language processing skills are making it a flexible AI tool that is revolutionizing a number of industries and spurring innovation. All these industries – healthcare, petroleum and cybersecurity – handle large amounts of data that is sensitive that must be collected, stored, and processed in real time to make decisions. By extension and as AI continues to mature, there is still much that AI can do for these industries, but the key to this is going to be the establishment of more concrete and measurable ethics and rules of operation. In this abstract, the prospect of using Artificial Intelligence in healthcare, petroleum fraud, and cybersecurity is presented, along with the focus on the ethical issues in this process for proper and fair AI implementation.